Clinical-surgical characteristics of Peruvian patients undergoing appendectomy. A systematic review. - Zúñiga Baca, Dalmiro (2024)
Objective: to describe the clinical and surgical characteristics of Peruvian patients who have undergone appendectomy. Material and methods: A systematic review of the databases PubMed, Scopus, Web of Science, Virtual Health Library, and Scielo was carried out following the PRISMA guidelines. A protocol registered in the Prospective International Registry of Systematic Reviews (PROSPERO) database under the number CRD4202424517668 was followed. The search ended on January 24, 2024. All published articles have variables on clinical manifestations, stages of appendicitis, operative technique, operative time, postoperative diagnosis, operative site infection, and hospital stay. Results: 217 studies were identified from the database search, and 10 observational studies that met the inclusion criteria were included. A total of 1766 patients undergoing appendectomy were included (53.45% male, mostly aged 25–40 years). Postoperative manifestations included pain, nausea, and vomiting. The most common stages of appendicitis were congestive (10%), phlegmonous (20%), and necrotic (22%). Laparoscopic technique was used in 35%, open in 53%, with a mean duration of 72 minutes. Diagnosis identified complicated appendicitis in 21% and uncomplicated appendicitis in 36%. Operative site infection was recorded in 7%, and the mean hospital stay was 3.67 days. Conclusions: The current study summarizes the clinical and surgical characteristics of patients who have undergone appendectomy. The implementation of preventive strategies with the aim of reducing possible postoperative complications is recommended.